Social stratification and cultural consumption: attending theatre and dance performances in Athens - Καυταντζόγλου, Ρωξάνη; Εμμανουήλ, Δημήτρης (The Greek Review of Social Research, 2016)
The article focuses on the relationship between social stratification and consumption of culture, namely the performative arts (theatre and dance) and the choice of their genres. The research findings are interpreted in light of the ongoing debate between P. Bourdieu’s theory of Distinction, the post-modernists’ individualisation argument, R. Peterson’s omnivore model and B. Lahire’s theory of cultural dissonance. The neo-weberian distinction between status and socio-economic class constitutes a central methodological tenet of our approach. While our findings indicate the partial prevalence of the distinction mechanism advanced by Bourdieu, it should also be noted that they do not support the bourdieusan systematic ‘homology’ between class and culture. Tendencies toward omnivorousness and cultural dissonance are present, albeit at very low rates.